Gender stereotypes in the physical education textbook - Vicki Ahmad Karisman; Dedi Supriadi; Gita Febria Friskawati (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Gender stereotypes in media, including books, can play an important role in the process of gender identity construction. The purpose of this study is to analyze gender representation in Elementary School Physical Education, Sports and Health textbooks. The analysis was conducted by tabulating images and looking at the appearance of gender characters in the text in the elementary physical education books from grade one to grade six. Visibility and Firstness refer to the number of times a male or female character appears first in an exercise. Gender stereotypes (such as female characters doing rope games, male characters playing big ball games) were counted. Based on this data, it can be seen that in classes 1,2,4,5 and 6 there are more male images than female, only in class 3 there are more female images than male. Furthermore, the results of Gender Stereotyping data show that males are more dominant in Floor Gymnastics, Water Sports, Physical Fitness Activities, Invasion Games, Net Games, Maintenance of Reproductive Hygiene, Pencak Silat Martial Arts, and Athletics. In contrast gymnastics materials and Rhythmic Gymnastics Activities are dominated by women. Such stereotypes are considered as one of the ways in which gender identity is influenced and constructed. They can limit individuals' choices in relation to their roles, interests and aspirations, as individuals tend to conform to what is perceived as the gender norm in society.